Mito da Chuva como elemento de Identidade nas comunidades Tapera/ Boa Esperanca - Anjos, María dos Adeodata (2012)
The people from the hinterland is the true picture of their biome. It is with the biome they learn to live with the new conditions of change where the main feature is the resistance. Their "hibernation" occurs in the summer and "blooming" in the winter. To resist the phenomenon of drought the human being finds spaces in the cosmology. He creates the cosmography by describing everything about him and gives meaning to life making these elements from the myths, legends and rites enriching them a vast symbolism, because the human being always will always be a social semiotic. Through sign search direction for the various relationships and situations that surround them. According to R Jakoson, the man identifies himself with the environment and the social environment for these give meaning to “Himself” that was lost in the whole of cosmic nature. The range of meanings given to the elements by the inhabitants of the countryside is the answer that even in the midst of modern situations has a culture and thought itself and constituted by particular climate and vegetation, and the creation of these two phenomenon are part of the constitution and characterization of these people, and makes creative beings and in this picture comes and goes in the nature of thoughts seeking the answers to your questions. This is how the prophets of rain are forecast winter of each year in this region, January-May, through codes, symbols that are being inter-related with myths and interspersed with rituals. The secret of all this are the “Retornos” that give meaning to the answers deciphered through signs. "When I was a little woman I spent all the night watching the lightning" (Chico Leiteiro from Quixadá-CE). The signals used are the elements that respond the needs that are ignored by those who have no link with the hinterland. Even before the modern mythology that fascinate and involve a lot of the youth, traditional cultures try to find ways to resist. His influence still pervades with enough force amid the traditional hinterland communities that remain faithful to its forecast of winter through the bar Christmas (winter solstice) the path of St. James (milk-way), Southern Cross, among other signs cosmological, which are deciphered by the sensitivity that these communities are in relationship with the biosphere and the stars.